Study on population distribution of Mahakaushali goat and socio-economic status of goat farmers in Seoni, Chhindwara and Balaghat districtsof Madhya Pradesh - VANDRE, RAJESH KUMAR; RAJPUT, NEETU; JHA, AMIT KUMAR; SEN, SULOCHANA; DAS, BHABESH CHANDRA; DIXIT, BALESHWARI; TOMAR, SERLENE; RAWAT, KAVITA; GUPTA, NITIN MOHAN; TRIPATHY, SNEHA (The Indian Journal of Animal Sciences, 2025)
The study of the socio-economic status of farmers and distribution of the Mahakaushali goat population was conducted in Seoni, Chhindwara and Balaghat districts of Mahakaushal region of Madhya Pradesh, located in central India. It lies in the Narmada River valley at the upper or eastern reaches of Madhya Pradesh. The standard questionnaires recommended by NBAGR were used for the data collection. The data were collected through personal interviews with 625 goat farmers in the targeted districts. In the present study, farmers were interviewed for the demographic evaluation. The present study revealed that goat farmers of the targeted districts were economically poor, and they mainly depended upon the livestock for their livelihood (especially goat). The study specified that the Mahakaushali goat population was distributed across the Seoni, Chhindwara, and Balaghat districts of the Mahakaushal region in Madhya Pradesh. Based on the present study, the estimated local goat populations (Mahakaushali goat) were found 47370, 41070, and 59520, respectively, in Seoni, Balaghat, and Chhindwara districts. This survey was the first attempt to study the demographic and geographical distribution of the Mahakaushali goat in Seoni, Chhindwara and Balaghat districts of the Mahakaushal region of Madhya Pradesh.